2017
DOI: 10.3892/ijmm.2017.3114
|View full text |Cite
|
Sign up to set email alerts
|

Isoastragaloside I inhibits NF-κB activation and inflammatory responses in BV-2 microglial cells stimulated with lipopolysaccharide

Abstract: The excessive activation of microglia in many neurodegenerative diseases is detrimental to neuronal survival. Isoastragaloside I (ISO I) is a natural saponin molecule found within the roots of Astragalus membranaceus, a famous traditional Chinese medicine. In the present study, the anti‑inflammatory effects and the mechanisms of action of ISO I on activated BV-2 cells stimulated with lipopolysaccharide (LPS) were investigated. ISO I dose‑dependently inhibited the excessive release of nitric oxide (NO) and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…33 Moreover, formononetin, 34 calycosin, 35 and soyasaponin I 36 have been reported to significantly inhibit the NO production; therefore, the active ingredients of both AR and HR were considered. Ononin, 37 astragaloside IV, 38 and isoastragaloside I 39 in AR and indolelactic acid 40 and afromosin 41 in HR have also reported the function in the NO production inhibition, which may be related to the anti-inflammatory activity of AR and HR.…”
Section: Anti-inflammatory Activity Of Ar and Hrmentioning
confidence: 95%
“…33 Moreover, formononetin, 34 calycosin, 35 and soyasaponin I 36 have been reported to significantly inhibit the NO production; therefore, the active ingredients of both AR and HR were considered. Ononin, 37 astragaloside IV, 38 and isoastragaloside I 39 in AR and indolelactic acid 40 and afromosin 41 in HR have also reported the function in the NO production inhibition, which may be related to the anti-inflammatory activity of AR and HR.…”
Section: Anti-inflammatory Activity Of Ar and Hrmentioning
confidence: 95%
“…They are typical cycloartane triterpene glycoside structures with the same parent nucleus as cycloastragalus alcohol (tetracyclic triterpenoids) and several glycoside groups [ 25 ]. It has been reported that tetracyclic triterpenoids have pharmacological activity by enhancing nonspecific immune responses and reversing the immunosuppressive effect of chemotherapeutic drugs to achieve antitumor effects [ 26 ]. Astragaloside IV, a representative component of cycloastragalus alcohol saponins in AR, has dual activities as astragalus polysaccharides and terpenes [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Astragaloside IV promotes mitochondrial autophagy, thus reducing the accumulation of damaged mitochondria and the production of mitochondrial reactive oxygen species. 14,[96][97][98][99][100][101][102][103] To conclude, the mechanism of Astragali Radix against aging-related neurodegenerative diseases mainly involves anti-neurotoxicity, anti-neuroinflammation and antioxidation. Astragali Radix is a dietary herb, applied with many potential signal regulations, including neurotransmitters and receptors, anti-inflammatory activity, inhibiting amyloid aggregation, inducing myelin repair and neurogenesis, and activating signal pathways related to neurological diseases.…”
Section: Astragali Radixmentioning
confidence: 99%